Study of Textural Characteristics of The Surface Sediments along Al- Ramel Al- Janobi coast- Latakia- Syria (Latakia University Journal -Basic Sciences Series, 2020)
The study area is located at the north-  west  of Al Kaber river estuary along (800m). This area has been studied to determine the grain size spectrum and textural parameters (mean, sorting, skewness and kurtosis). Four sediment types were identified. These are (Sandy Gravel;  Gravelly Sand; Slightly Gravelly Sand; Sand) reflecting the difference between the region and the effect of the river on the sediment distribution. Texturally, sediments are medium sand away from the shoreline and gravel in the areas under the influence of the river and fine sands at the depth that range between (1.5 , 2.5m), well sorted to moderately well sorted, very negatively skewed, and mesokurtic. Liner discriminate function analysis (LDF) of the sample indicates an Aeolian, beach deposition environment and less influence of fluvial. The dominate mode of transport is floating and suspended transport. These parameters confirm that the sediments were deposited under moderate to high energy conditions. This condition vary from place to another according to the place of deposition and the severity of the kinetic energy.